Weed management in millets - Mishra, J. S.; Kumar, Rakesh; Upadhyay, P. K.; Hans, Hansraj (Indian Farming, 2018)
Due to slow initial growth and wider row spacing, millets are heavily infested with weeds especially during rainy season. In most of millets, initial period of 4-6 weeks after seedling emergence was found critical. Uncontrolled weed infestation reduce crop yield by 15 to 83% in sorghum, 16 to 94% in pearl millet, and 55 to 61% in finger millet. Crop rotation with trap crop/catch crops i.e. soybean and cotton, and intercropping of sorghum /pearl millet with groundnut, soybean and cowpea and green-manuring crops like Sesbania help in reducing the weed problem including parasitic weed Striga spp. Integration of pre-emergence herbicides and intercultural operations(hoeing and hand weeding) at 30 to 35 days after sowing provides effective and economical weed control in semiarid regions.